Estimating Young’s Modulus and Modulus of Rupture of Coconut Logs using Reconstruction Method - Bahtiar E.T.; Nugroho N.; Surjokusumo S. (Institute of Research and Community Outreach - Petra Christian University, 2010)
This research develops a theory of the so called reconstruction method to estimate the Young’s modulus (E) and modulus of rupture (SR) of coconut logs. The reconstruction method includes among others; flexure test on small-clear specimens, which were taken from locations distributed along the horizontal as well as vertical direction inside the logs. Further, the estimated E and SR were acquired by arranging systematically each of the small clear specimens as if back in the original location in the logs. The estimation was assisted by mechanical theory, statistics (best fit multiple regression equations), mathematics (calculus), and geometry approach. This reconstruction method successfully estimates E and SR of the coconut logs. The average estimated E and SR value as acquired from tree sample number 1 and 2 were 8,118– 8,596 MPa, and 118–124 MPa, respectively. Those two values were still comparable to common US wood species used for construction i.e. 6,660–15,000 MPa (for E); and 58–132 MPa (for SR). Moreover those estimations of E and SR correlated significantly with each other. This again strengthens the reliability and representativeness of the E and SR values for coconut logs as acquired using the proposed reconstruction methods.